2021
DOI: 10.1136/rmdopen-2021-001755
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microbiota changes induced by TNF-inhibitors in IBD-related spondyloarthritis

Abstract: BackgroundThe close relationship between joints and gut inflammation has long been known and several data suggest that dysbiosis could link spondyloarthritis (SpA) to inflammatory bowel diseases (IBD). The introduction of biological drugs, in particular tumour necrosis factor inhibitors (TNFi), revolutionised the management of both these diseases. While the impact of conventional drugs on gut microbiota is well known, poor data are available about TNFi.AimTo investigate the impact of TNFi on gut microbiota.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 61 publications
(80 reference statements)
0
15
0
Order By: Relevance
“…Like AZA, the anti-TNF-α antibody can restore intestinal microbial diversity in patients with Crohn’s disease by decreasing Proteobacteria but increasing Bacteroidetes ( Effenberger et al., 2021 ). In 20 enteropathic arthritis patients who followed a Mediterranean diet, anti-TNF-α antibody treatment for 6 months could increase Lachnospiraceae family and Coprococcus genus and also induce a decreasing trend in Proteobacteria and Gammaproteobacteria and an increasing trend in Clostridia ( Ditto et al., 2021 ).…”
Section: The Effects On the Gut Microbiota Of Therapeutic Agents For Gd/gomentioning
confidence: 99%
“…Like AZA, the anti-TNF-α antibody can restore intestinal microbial diversity in patients with Crohn’s disease by decreasing Proteobacteria but increasing Bacteroidetes ( Effenberger et al., 2021 ). In 20 enteropathic arthritis patients who followed a Mediterranean diet, anti-TNF-α antibody treatment for 6 months could increase Lachnospiraceae family and Coprococcus genus and also induce a decreasing trend in Proteobacteria and Gammaproteobacteria and an increasing trend in Clostridia ( Ditto et al., 2021 ).…”
Section: The Effects On the Gut Microbiota Of Therapeutic Agents For Gd/gomentioning
confidence: 99%
“…In mice, etanercept treatment restored intestinal microbiota composition similar to control mice (174). YIN et al ( 19) and Maria et al (175) found that TNFi treatment substantially restored the disturbed microbiome observed in untreated AS Potential methods for therapeutic intervention targeting the gut microbiota. Antibiotics may eliminate harmful bacteria in the gut.…”
Section: Biologicsmentioning
confidence: 88%
“…( 19 ) and Maria et al. ( 175 ) found that TNFi treatment substantially restored the disturbed microbiome observed in untreated AS cases, including several critical bacterial species previously associated with AS and other related diseases, compared to HCs. In a study exploring responses to anti-TNF-α therapy, AS patients had a lower microbiota diversity at baseline than HCs at the same level but returned to normal after one month of treatment ( 12 ).…”
Section: Targeted Gut Microbiota Therapy In Preventing or Treating Asmentioning
confidence: 95%
“…Moreover, in HLA-B27-positive transgenic rats, Prevotella dysregulates the key pathogenic cytokines, including IL-17, IL-23, and TNF-α [42,43]. Blautia [44], Odoribacter [45], Rikinella [43,46], Bacteroides [47,48], Parabacteroides [17,49], Desulfovibrio [50,51], Streptococcus [52][53][54][55], and Clostridia [56][57][58][59] are associated with the dysbiosis in patients with SpA and/or in animal models of the human disease. Most of these bacteria primarily have pro-inflammatory potential; Desulfovibrio and Parabacteroides [60,61] also have anti-inflammatory potential.…”
Section: Plos Onementioning
confidence: 99%